Initial Afferent Lymphatic Vessels Controlling Outbound Leukocyte Traffic from Skin to Lymph Nodes - Melero, Ignacio; Teijeira, Alvaro; Rouzaut, Ana (Frontiers in Immunology, 2013)
Tissue drains fluid and macromolecules through lymphatic vessels, which are lined by a specialized endothelium that expresses peculiar differentiation proteins, not found in blood vessels (i.e: LYVE-1, Podoplanin, PROX-1 and VEGFR-3). Lymphatic capillaries are characteristically devoid of a continuous basal membrane and are anchored to the ECM by elastic fibers that act as pulling ropes which open the vessel to avoid oedema if tissue volume increases, as it occurs upon inflammation. Lymphatic vessels are also crucial for the transit of T lymphocytes and antigen presenting cells from tissue to draining lymph nodes. Importantly, cell traffic control across lymphatic endothelium is differently regulated under resting and inflammatory conditions. Under steady-state non-inflammatory conditions, leukocytes enter into the lymphatic capillaries through basal membrane gaps (portals). This entrance is integrin-independent and seems to be mainly guided by CCL21 chemokine gradients acting on leukocytes expressing CCR7. In contrast, inflammatory processes in lymphatic capillaries involve a plethora of cytokines, chemokines, leukocyte integrins and other adhesion molecules. Importantly, under inflammation a role for integrins and their ligands becomes apparent and, as a consequence, the number of leukocytes entering the lymphatic capillaries multiplies several-fold. Enhancing transmigration of dendritic cells en route to lymph nodes is conceivably useful for vaccination and cancer immunotherapy, whereas interference with such key mechanisms may ameliorate autoimmunity or excessive inflammation. Recent findings illustrate how, transient cell-to-cell interactions between lymphatic endothelial cells and leukocytes contribute to shape the subsequent behaviour of leukocytes and condition the lymphatic vessel for subsequent trans-migratory events.